2012
DOI: 10.1016/j.smallrumres.2012.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Changes in goat milk fatty acids during abrupt transition from indoor to pasture diet

Abstract: 14Goal of this study was to evaluate the kinetics of goat milk fatty acids during abrupt 15 transition from indoor to pasture-based diets. Twelve Valdostana goats in mid-lactation 16 reared indoors and fed hay and concentrates for 40 days were abruptly brought outdoors 17 on natural pasture and fed fresh grass ad libitum. Feed samples and individual milk 18 samples were collected for fatty acids analysis on the last day of indoor feeding (day 0) 19 and after 1, 2, 3, 4, 6, 9, 13, 18 and 23 days of fresh grass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 24 publications
0
24
0
1
Order By: Relevance
“…It is well known that fresh grass feeding positively affects the lipid fraction of goat milk by enhancing the presence of health-promoting fatty acids (FA) (e.g.,rumenic and vaccenic acids, and contemporarily lowering the omega-6/omega-3 FA ratio and the levels of specific FA considered detrimental for human health (e.g., hypercholesterolaemic medium-chain saturated FA) (Renna et al, 2012a(Renna et al, , 2012bMancilla-Leytón et al, 2013). Besides that, in the last decade it has also been repeatedly demonstrated that the FA composition of milk and cheese from grazing ruminants may be significantly influenced by the botanical composition of the ingested plants (among others, Collomb et al, 2002;Di Trana et al, 2005;Renna et al, 2014a).…”
Section: " "mentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that fresh grass feeding positively affects the lipid fraction of goat milk by enhancing the presence of health-promoting fatty acids (FA) (e.g.,rumenic and vaccenic acids, and contemporarily lowering the omega-6/omega-3 FA ratio and the levels of specific FA considered detrimental for human health (e.g., hypercholesterolaemic medium-chain saturated FA) (Renna et al, 2012a(Renna et al, , 2012bMancilla-Leytón et al, 2013). Besides that, in the last decade it has also been repeatedly demonstrated that the FA composition of milk and cheese from grazing ruminants may be significantly influenced by the botanical composition of the ingested plants (among others, Collomb et al, 2002;Di Trana et al, 2005;Renna et al, 2014a).…”
Section: " "mentioning
confidence: 99%
“…The same group of goats foraged on both vegetation types to exclude confounding effects related to differences in selection behaviour among individuals (Provenza et al, 2003). To minimize the effect of the physiological stage of the animals on their intake behaviour, the time period between OG and GF exploitation was reduced at the minimum (22 days) required to adapt to such different vegetation types, especially for stabilization of FA in goat milk fat (Renna et al, 2012b). For the latter purpose, before entering the enclosures the goats grazed for three weeks two grazing lands dominated by grasses and shrubs similar to OG and GF, respectively.…”
Section: " "mentioning
confidence: 99%
“…In fact, grazing improves the milk's characteristics, also due to the increased concentrations of polyunsaturated fatty acids (PUFA) in milk (e.g. omega-3 FA and conjugated linoleic acid), which are known to have many beneficial effects on human health (Biondi et al 2008;Renna et al 2012;Albenzio et al 2016). Omega-3 (n-3) fatty acids (FAs) are involved in the development of brain and retinal tissues and in the progression and prevention of human pathologies, including heart disease and some cancers (Blondeau 2016).…”
Section: Introductionmentioning
confidence: 99%
“…previously reported increases of these FA levels 12 h after LO supplementation in dairy goats. Further investigations have reported increases 24 h after feeding diets rich in α ‐linolenic acid . The trends of cis ‐9, trans ‐11, cis ‐15 18:3 contents in milk fat (Table ) reflected those of α ‐linolenic acid.…”
Section: Resultsmentioning
confidence: 99%